Distribution and Function of Glycosaminoglycans and Proteoglycans in the Development, Homeostasis and Pathology of the Ocular Surface - Puri, Sudan; Coulson-Thomas, Yvette M.; Gesteira, Tarsis F.; Coulson-Thomas, Vivien J. (Frontiers in Cell and Developmental Biology, 2020)
The ocular surface, which forms the interface between the eye and the external environment, includes the cornea, corneoscleral limbus, the conjunctiva and the accessory glands that produce the tear film. Glycosaminoglycans (GAGs) and proteoglycans (PGs) have been shown to play important roles in the development, hemostasis and pathology of the ocular surface. Herein we review the current literature related to the distribution and function of GAGs and PGs within the ocular surface, with focus on the cornea. The unique organization of ECM components within the cornea is essential for the maintenance of corneal transparency and function. Many studies have described the importance of GAGs within the epithelial and stromal compartment, while very few studies have analyzed the ECM of the endothelial layer. Importantly, GAGs have been shown to be essential for maintaining corneal homeostasis, epithelial cell differentiation and wound healing, and, more recently, a role has been suggested for the ECM in regulating limbal stem cells, corneal innervation, corneal inflammation, corneal angiogenesis and lymphangiogenesis. Reports have also associated genetic defects of the ECM to corneal pathologies. Thus, we also highlight the role of different GAGs and PGs in ocular surface homeostasis, as well as in pathology.